2017
DOI: 10.1007/s40477-017-0247-4
|View full text |Cite
|
Sign up to set email alerts
|

Copeman nodule: a case report

Abstract: The Copeman nodule is a disease of the subcutaneous soft tissue consisting in subcutaneous adipose tissue herniation through the superficial muscular fascia. A 30-year-old female patient presented with chronic left pain just above the iliac crest. Ultrasound examination showed subcutaneous adipose tissue herniation through the superficial muscular fascia with a hernia gap of 15.9 mm in diameter. Then the patient underwent surgery under local anesthesia with suturing of the hernia gap and immediate regression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…According to him (personal communication by an email), he adopted this sobriquet from Dr Henry Wyatt, his instructor in London, who taught him that one of the characteristics of these nodules was their mobility under the examining fingers ' 'like a scurrying mouse' '. Curtis adopted the term to make it easy for medical students, doctors, and patients to explain this entity Miscellaneous ' 'Copeman's nodule' ' and ' 'Copeman and Ackerman's syndrome' ' are also terms that have been used due to Copeman's influence on the study of the nodules [4,32,70] Table 3 Main clinical features related to painful lumbar nodules according to Copeman's view [11][12][13][14]51] Low back pain symptoms caused by fatty nodules Localization Pain is usually felt in an imprecise location in the vicinity of the sacroiliac joints, and the patient is often unaware that it may come from a painful nodule. Palpation upon the area may help the hesitant patient to better localize a specific nodule.…”
Section: Back Micementioning
confidence: 99%
See 2 more Smart Citations
“…According to him (personal communication by an email), he adopted this sobriquet from Dr Henry Wyatt, his instructor in London, who taught him that one of the characteristics of these nodules was their mobility under the examining fingers ' 'like a scurrying mouse' '. Curtis adopted the term to make it easy for medical students, doctors, and patients to explain this entity Miscellaneous ' 'Copeman's nodule' ' and ' 'Copeman and Ackerman's syndrome' ' are also terms that have been used due to Copeman's influence on the study of the nodules [4,32,70] Table 3 Main clinical features related to painful lumbar nodules according to Copeman's view [11][12][13][14]51] Low back pain symptoms caused by fatty nodules Localization Pain is usually felt in an imprecise location in the vicinity of the sacroiliac joints, and the patient is often unaware that it may come from a painful nodule. Palpation upon the area may help the hesitant patient to better localize a specific nodule.…”
Section: Back Micementioning
confidence: 99%
“…However, the Italian radiologists Farina et al published a case report in the same year, in which an observed nodule was found to be a well-circumscribed hypoechoic image of herniated fatty tissue through a hernial gap in muscular fascia. The patient’s low back pain resolved after nodule excision with closing of the gap [ 4 ].…”
Section: The Most Recent Publications Related To Sonographic Studiesmentioning
confidence: 99%
See 1 more Smart Citation